PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGE - Iffa Lathifah Nur Haliza Putri, - (2019)
This study aims to determine the effect of Capital Structure proxied by Debt to Equity Ratio (DER), Profitability proxied with Return On Equity (ROE), and Firm Growth proxied by Asset Growth toward Firm Value proxied by Price to Book Value (PBV). Population in this study are manufacture companies of food and beverages sub sector listed in Indonesia Stock Exchange (IDX) 2014-2017. The technique of determination of the sample using the method of purposive sampling and obtained 11 food and beverage sub-sector companies with a research period of four years to obtain 44 units of samples. Data analysis was done using Microsoft Excel 2016 and hypothesis testing in this research using Data Panel Regression Analysis with EViews 9.0 program and significance level of 5%. The result of the research shows that (1) capital structure (DER) has positive effect on firm value (PBV), (2) profitability (ROE) has a positive effect on firm value (PBV), (3) firm growth (ASSET GROWTH) no effect on firm value (PBV).